Alternative and controversial treatments - Smith, Tristram (Henry Stewart Talks, 2010)
Alternative and controversial treatments, Prevalence in autism community, Research evidence, Sensory-motor therapies, Bonding therapies, Complementary and alternative medicine such as diets, nutritional supplements, Hyperbaric Oxygen Therapy, chelation, and withholding of vaccines
Archived at 2021/09/29